Evaluation of the in vitro biocompatibility of orthodontic elastics - Matheus Melo Pithon; Rogério Lacerda dos Santos; Fernanda Otaviano Martins; Maria Teresa Villela Romanos; Mônica Tirre de Souza Araújo (Universidade Estadual de Campinas, 2015)
Aim: Latex has been extensively used in orthodontics since the advent of the specialty. Natural latex does not fall into the category of materials known to be entirely inoffensive. The objective of the present in vitro study is to test the hypothesis that there is no difference in the cytotoxicity between natural latex elastics of different colors. Methods: The present article compared different latex intra-oral elastics (5/16 = 7.9 mm, mean load). The samples were divided into six groups of 15 elastics according to their manufacturer: Groups N, Y, V, R, G and P (Uniden, natural latex elastics and colored elastics, namely, yellow, violet, red, green and pink, respectively). Cytotoxicity assays were performed by using cell culture medium containing cells from mouse fibroblast cell line L929. The cytotoxicity was evaluated by using the "dye-uptake" test, which was employed at two different moments (1 and 24 h). Data were compared by ANOVA and Tukey's test (P < 0.05). Results: There was statistically significant difference (P < 0.05) between the groups N, Y, V, R, G, P and the cell control at 1 h. After 24 h, a decrease in cell viability was observed in all groups. There was statistically significant difference (P < 0.05) between all test elastics groups and the cell control at 24 h. No statistically significant difference (P >0.05) was found among the test elastics groups at 24 h. Conclusion: Latex elastics from natural, yellow, violet and red colors induced a lowest amount of cell lysis compared to the elastics green and pink colors at 1 h, all latex elastics were found to be highly cytotoxic, regardless of their color at 24 h.